2021
DOI: 10.1038/s41598-021-02016-5
|View full text |Cite
|
Sign up to set email alerts
|

Different contributions of efferent and reafferent feedback to sensorimotor temporal recalibration

Abstract: Adaptation to delays between actions and sensory feedback is important for efficiently interacting with our environment. Adaptation may rely on predictions of action-feedback pairing (motor-sensory component), or predictions of tactile-proprioceptive sensation from the action and sensory feedback of the action (inter-sensory component). Reliability of temporal information might differ across sensory feedback modalities (e.g. auditory or visual), which in turn influences adaptation. Here, we investigated the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(49 citation statements)
references
References 55 publications
(144 reference statements)
3
45
1
Order By: Relevance
“…Indeed, flexible recalibration of the perceived relative timing between actions and their sensory outcomes is an established phenomenon known as sensorimotor temporal recalibration. Evidence for this phenomenon can be derived from a range of studies that aimed at inducing a sensorimotor temporal recalibration effect (TRE) by repeatedly inserting a constant delay between a participant’s action (like a button press) and its sensory outcome in form of a light flash or a brief tone ( Stetson et al, 2006 ; Heron et al, 2009 ; Sugano et al, 2010 , 2012 , 2016 , 2017 ; Stekelenburg et al, 2011 ; Tsujita and Ichikawa, 2012 ; Rohde and Ernst, 2013 ; Elijah et al, 2016 ; Cao et al, 2017 ; Cai et al, 2018 ; Arikan et al, 2021 ). After repeated exposure to such a manipulation, the delayed action-outcome was in fact perceived as occurring synchronously with the action ( Sugano et al, 2010 , Keetels and Vroomen, 2012 ; Sugano et al, 2012 , 2016 , 2017 ; Yamamoto and Kawabata, 2014 ) and shorter delays were less likely to be detected ( Arikan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, flexible recalibration of the perceived relative timing between actions and their sensory outcomes is an established phenomenon known as sensorimotor temporal recalibration. Evidence for this phenomenon can be derived from a range of studies that aimed at inducing a sensorimotor temporal recalibration effect (TRE) by repeatedly inserting a constant delay between a participant’s action (like a button press) and its sensory outcome in form of a light flash or a brief tone ( Stetson et al, 2006 ; Heron et al, 2009 ; Sugano et al, 2010 , 2012 , 2016 , 2017 ; Stekelenburg et al, 2011 ; Tsujita and Ichikawa, 2012 ; Rohde and Ernst, 2013 ; Elijah et al, 2016 ; Cao et al, 2017 ; Cai et al, 2018 ; Arikan et al, 2021 ). After repeated exposure to such a manipulation, the delayed action-outcome was in fact perceived as occurring synchronously with the action ( Sugano et al, 2010 , Keetels and Vroomen, 2012 ; Sugano et al, 2012 , 2016 , 2017 ; Yamamoto and Kawabata, 2014 ) and shorter delays were less likely to be detected ( Arikan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this phenomenon can be derived from a range of studies that aimed at inducing a sensorimotor temporal recalibration effect (TRE) by repeatedly inserting a constant delay between a participant’s action (like a button press) and its sensory outcome in form of a light flash or a brief tone ( Stetson et al, 2006 ; Heron et al, 2009 ; Sugano et al, 2010 , 2012 , 2016 , 2017 ; Stekelenburg et al, 2011 ; Tsujita and Ichikawa, 2012 ; Rohde and Ernst, 2013 ; Elijah et al, 2016 ; Cao et al, 2017 ; Cai et al, 2018 ; Arikan et al, 2021 ). After repeated exposure to such a manipulation, the delayed action-outcome was in fact perceived as occurring synchronously with the action ( Sugano et al, 2010 , Keetels and Vroomen, 2012 ; Sugano et al, 2012 , 2016 , 2017 ; Yamamoto and Kawabata, 2014 ) and shorter delays were less likely to be detected ( Arikan et al, 2021 ). This indicates recalibration of the expected relative timing between action and outcome leading to a shift of synchrony perception toward the exposed delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…less modality transfer for direct compared to indirect feedback, Schmitz & Bock, 2014 ). Additionally, it has recently been shown that motor-visual and motor-auditory recalibration are, to a certain extent, driven by different components (reafferent and efferent, respectively, Arikan, van Kemenade, Fiehler, Kircher, Drewing, & Straube, 2021 ), and transfer (or the lack thereof) between modalities can be explained by differential adaptation of these components. Thus, our finding of modality-specific temporal adaptation could also be a manifestation of the differential use of these components.…”
Section: Discussionmentioning
confidence: 99%
“…Whether motor-recalibration in one modality transfer to other modalities seems to be highly dependent on task similarity (e.g., no task-transfer within modality, de la Malla et al, 2014;modality-transfer within task, Sugano et al, 2010), or how performance feedback is presented (e.g., less modality transfer for direct compared to indirect feedback, Schmitz & Bock, 2014). Additionally, it has recently been shown that motor-visual and motor-auditory recalibration are, to a certain extent, driven by different components (reafferent and efferent, respectively, Arikan et al, 2021), and transfer (or the lack thereof) between modalities can be explained by differential adaptation of these components.…”
Section: Discussionmentioning
confidence: 99%